ROSY application for selecting R packages that perform ROC analysis - Quintas, José Pedro (2020)
The empirical ROC curve is a powerful statistical tool to evaluate the precision of tests in several fields of study. This is a two-dimensional plot where the horizontal and vertical axis represent false positive and true positive fraction respectively, also referred to as 1-specificity and sensitivity, where precision is evaluated through a summary index, the area under the curve (AUC). Several computer tools are used to perform this analysis one of which is the R environment, this is an open source and free to use environment that allows the creation of different packages designed to perform the same tasks in distinct ways often resulting in different customization and features often providing similar results. There is a need to explore these different packages to provide an experienced user with the simplest and most robust execution of a needed analysis. This work catalogued the different R packages capable of ROC analysis exploring their performance. A shiny web application is presented that serves as a repository allowing for efficient use of all of these packages.